ETHICAL CHALLENGES IN THE CONSERVATION OF THE WALL PAINTINGS OF CHAPEL 11 AT THE SACRO MONTE DI VARALLO - Piqué, Francesca; Jean, Giacinta (Protection of Cultural Heritage, 2019)
Chapel 11 is one of the 45 chapels of the Sacro Monte di Varallo. It is decorated with 16th century polychrome terracotta statues and wall paintings representing the Massacre of the Innocents. Since 2015, the University of Applied Sciences and Arts of Southern Switzerland (SUPSI) is in charge of its conservation. Up-close examination of the wall paintings allowed to observe the presence of overpainting, which were evaluated to have no aesthetical and/or technical quality. During the study phase and with preliminary tests for treatment development, it became clear that the removal of this overpaint was risky for the underlying original decoration. Moreover, it was not possible to determine if under the overpainting there was the original layer and in what condition it was. Although IR Reflectography showed the presence of underdrawings, this information did not always coincided with the presence of a paint layer. Considering that the overpainting covers about 80% of the surface, SUPSI strongly advised against embarking on its removal. This conclusion was achieved after several removal attempts and through regular communication meeting with the stakeholders aimed at illustrating the situation and the results achieved. SUPSI considered more ethical to focus on the development of a ‚reversible’ stabilization intervention considering that in the future new technologies (to assess the presence of paintings below and to remove overpainting) could make the recovery of what remains of the original decoration easier. This paper describes the project in terms of the ethical challenges faced when conflicting expectations about the project arised.